Performance of a virtual source model for stereotactic radiosurgery with a dynamic micro-multileaf collimator. - González-Infantes, Wilfredo; Anguiano, Marta; Lallena, Antonio (IOP, 2017)
A virtual source model recently developed for external radiotherapy, which includes two photon sources and two electron sources, is tested for stereotactic radiosurgery with a dynamic micro-multileaf collimator. A 6 MV Elekta Precise linac that incorporates a 3Dline L’Arancio dynamic micro-multileaf collimator was considered. The capabilities of the virtual source model have been tested against full simulations performed with the Monte Carlo simulation code PENELOPE using both PENELOPE itself and the rapid Monte Carlo code DPM. The reference 10 cm × 10 cm radiation field as well as small fields of 1.2 cm × 1.2 cm, 2.9 cm × 2.9 cm and 5.8 cm×5.8 cm were considered. The dynamic micro-multileaf collimator effect can be included in the virtual source model by reducing the width of the photon primary source by a factor 3. In all cases the virtual source model simulations were in very good agreement with the complete ones including the linac and collimator geometries.
https://publishingsupport.iopscience.iop.org/questions/what-is-iop-publishings-green-open-access-policy/
Keywords: Óptica; Estereoencefalotomía; virtual source model; micro-multileaf collimator; stereotactic radiosurgery